Retracted: Pengenalan Industri 4.0 di SMK Taman Siswa Palembang - R.A Nurul Moulita; Faizah Suryani; Marthin Luther King; Rita Maria Veronika; Madagaskar (CV. Doki Course and Training, 2024)
Following up on the findings of the CV. Doki Course and Training Management team regarding indications of articles published in Rumah Jurnal CV. Doki Course and Training on Bersama : Jurnal Pengabdian Masyarakat Vol. 2 No. 2 (2024) published on December 28, 2024 with the title: Pengenalan Industri 4.0 di SMK Taman Siswa Palembang at the link: https://jurnal.dokicti.org/index.php/bersama/article/view/810. Because of the research results of CV. Doki Course and Training management and journal managers. That the authors published in our journal have committed Academic Integrity Violations in the form of Plural Submissions: https://anjani.kemdikbud.go.id/contents/pengajuan-jamak-76037816. Evident from: Articles published in Pengabdian Masyarakat Sumber Daya Unggul Vol. 2 No. 4 (2024) published on December 29, 2024 at the link: https://publikasi.abidan.org/index.php/pmsdu/article/view/581. After we held an internal coordination meeting, the follow-up from the management of CV. Doki Course and Training was to retract the article with the title: Pengenalan Industri 4.0 di SMK Taman Siswa Palembang at the link: https://jurnal.dokicti.org/index.php/bersama/article/view/810. CV. Doki Course and Training has also reported to https://anjani.kemdikbud.go.id/ officially through the CV. Doki Course and Training Account. Thus, this notification aims to maintain the quality of journal management at Rumah Jurnal CV. Doki Course and Training.